Ġucin ǰirġuġatu tayilburi toli = Gučinzurgaat tajlbar tolʹ = The Mongolian Explanatory Dictionary in 36 volumes - Sumʹjaabaatar, Baldandoržijn 1937- ("Žinst Hargana" Hėvlėlijn Gazar, 2003)
Mongolian explanatory dictionary which contains and expands upon the five-language Qing dictionary "Wu ti Qing wen jian. Romanized equivalents have been added to the Manchu entries, based on older classical dictionaries. Originally compiled between 1921 and 1927; volume VI [6] published first in 2003